Validitas Perangkat Pembelajaran Fisika Dengan Model Post Organizer Berbantuan Video - Sukma Fatiah; Ahmad Harjono; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2021)
The purpose of this study is to determine the validity of the physics learning devices with post organizer models assisted by videos. The research design used research and development (R & D) design with 4D model (define, design, develop, & disseminate). Learning tools developed are sylabus, lesson plan, learner worksheets, understanding of concept, and learning video. This paper only focused on the process of testing the validation of the contents and constructs of the learning tool. This study is restricted to limited testing by taking the results of validation from the validator and questionnaire of response from students. Validation results using CVR and CVI indicate learning tools in the very feasible categories and reliable. The results of limited trial show that studentsÃ¢â¬â¢ response of 99.94% and 98.31% with very good categories. So it can be concluded that tools with post organizer models assisted by learning videos are feasible and can be used in physics learning.